Ten Years On: Applying the Lessons of a Research Project in Thinking about the Practicalities of Research Design - Holló, Dorottya; Németh, Nóra (Working Papers in Language Pedagogy, 2009)
This paper reports on a loop project, i.e., it describes a research project and makes use of it for analysing the research methodology used in it with the aim of drawing attention to the importance of practicalities in research. The context of the analysis is a large scale and longitudinal research project on task based learning conducted in Hungary by researchers of Eötvös Loránd University, Budapest and the School of Education of the University of Leeds. To highlight some relevant practical issues and difficulties emerging in the course of conducting classroom research, the project in focus was compared with a “quasi-ideal” research process. This comparison found that the problems which often challenge the validity, reliability, credibility and dependability of research can be characterized as technical, circumstantial or professional. To counteract the effects of various disturbing occurrences, the suggested measures to take are: careful planning, constant revision and above all, a clear justification of every decision in the process. Whilst the paper focuses on classroom research, the issues raised can also serve as a lesson to researchers in other areas.